Effect of drying methods on the physicochemical composition and microstructure of pumpkin powders - Noui, Yassine; Lekbir, Adel; Bousselma, Abla; Haffas, Maamar; Hameurlaine, Samir (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
To increase the shelf life of fruit and vegetables, to be able to enjoy them in all four seasons, and to preserve their genetic make-up, drying has been found to be the best technique of conservation. The aim of this work is based on the study of the drying kinetics of pumpkin (Curcubita maxima) by two drying methods namely oven drying at a temperature of 60 °C and microwave drying at 180 W, with the purpose to model the drying kinetics of thin layers of pumpkin by four mathematical models (Two-Term, Modified Henderson and Pabis, Henderson Pabis and Bousselma et al.) and to study the effect of the two drying methods on the nutritional and microstructural properties of pumpkin powders. The results showed that the Microwave drying was faster than oven drying. The Modified Henderson and Pabis and Bousselma et al., models were chosen to adequately describe the drying behavior of oven- and microwave-dried thin pumpkin slices, respectively, due to a high R2 value and low χ2 and RMSE values. The physicochemical composition of the two powders (POD and PMD) was significantly different (p < 0.05) in terms of water content, pH, brix, lipids, and potassium. The analysis of the qualitative composition by FTIR did not show a change between the two powders. Similarly, the structure studied by SEM showed an identical and homogeneous structure. These powders have high nutritional properties, and their incorporation into foods should therefore be recommended.